PERBANDINGAN PERLINDUNGAN PENCARI SUAKA DAN PENGUNGSI DI INDONESIA DAN NEGARA LAIN BERDASARKAN HAK ASASI MANUSIA: Comparison Of The Protection Of Asylum Seekers And Refugees In Indonesia And Other Countries Based On Human Rights - Nuril Firdausiah; Fona Kartika Listiyapuji (Constitution Journal, 2023)
In principle, everyone has the right to move from one place to another, including leaving their own country and returning to their country. The problem of refugees is a quite complicated problem facing the world community today. In fact, everyone is guaranteed the right to seek and obtain asylum in another country to protect themselves from persecution. One form of population movement is displacement, both across countries and within the country's territory (Internal Displaced Persons). Displacement is a form of population movement that has different characteristics from other population movements, so it influences the protection mechanisms applied to them. In general, refugees are carried out because of the oppression of human rights in their country. Violations of human rights against an ethnic group by the country of origin force victims to flee to other countries to obtain protection so that both transit countries and destination countries that have not or have ratified the 1951 Convention must apply the principle of non-refoulement. Refugees are usually not provided with travel documents, so many experience abuse in their countries of origin, transit countries and destination countries. Each country is responsible for protecting refugees in their territory. To protect the rights and welfare of refugees, there is a special organization mandated by the United Nations ("UN"), namely the United Nations High Commissioner for Refugees (UNHCR). In order to handle the problem of asylum seekers and refugees as explained above, each country has its own regulations or policies. Based on the background above, this article will discuss further the comparison of regulations for the protection of asylum seekers and refugees in Indonesia and other countries. such as Thailand, Malaysia, Cambodia, Bangladesh and Australia as well as protection policies for asylum seekers and refugees based on human rights.   Absrtak Permasalahan mengenai pengungsi merupakan suatu persoalan yang cukup rumit yang dihadapi masyarakat dunia saat ini. Pada umumnya, pengungsian dilakukan karena terjadinya penindasan hak asasi manusia di negara mereka. Para pengungsi biasanya tidak dibekali dengan dokumen perjalanan sehingga banyak yang mengalami perlakuan sewenang-wenang baik di negara asal, negara transit, maupun negara tujuan. setiap negara bertanggung jawab untuk melindungi para pengungsi yang berada di wilayah teritorial mereka. Untuk melindungi hak-hak dan kesejahteraan pengungsi terdapat organisasi khusus yang diberikan mandat oleh Persatuan Bangsa-Bangsa (“PBB”), yaitu United Nations High Commissioner for Refugees (UNHCR). Dalam rangka menangani masalah pencari suaka dan pengungsi sebagaimana dijelaskan di atas maka masing-masing negara memiliki pengaturan atau kebijakannya masing-masing Berdasarkan latar belakang di atas, maka tulisan ini akan membahas lebih lanjut mengenai Perbandingan peraturan perlindungan pencari suaka dan pengungsi di Indonesia dan negara lain seperti thailand, malaysia, kamboja, bangladesh dan australia serta kebijakan perlindungan pencari suaka dan pengungsi berdasarkan hak asasi manusia.